The Impact of Globalization on Macroeconomic Stability and National Economic Policy in Developing Countries - Judijanto, Loso; Masyaili; Nun Arinal Haqqa El Mustafa; Izharuddin Pagala (PT. Anagata Sembagi Education, 2024)
This study aims to analyze the impact of globalization on macroeconomic stability and national economic policy in developing countries. Globalization has opened up various opportunities for developing countries in terms of international trade, foreign investment, and technology transfer, which can boost economic growth. However, the impact of globalization is uneven, with some developing countries being able to take advantage of it optimally, while others experience difficulties. There is an imbalance in the impact of globalization, where developing countries that are more integrated in the global economy tend to experience greater benefits, while those that are more isolated face greater challenges in terms of economic and policy stability. This study uses a quantitative approach with SPSS analysis tools to analyze data collected from 118 respondents in developing countries. The research discusses in depth how national economic policies can adapt to the changes brought by globalization, especially in terms of maintaining macroeconomic stability. The results are expected to provide an overview of the relationship between globalization and macroeconomic factors, as well as the economic policies needed to respond to the impact of globalization. The discussion in this study will focus on the challenges faced by developing countries, such as exchange rate fluctuations and inflation, and how fiscal and monetary policies can be optimized to create sustainable economic growth. The analysis will also provide policy recommendations to improve economic stability in the future